UrbanClap : a marketplace for on-demand services (B) - Mukherjee, Saral, (SAGE business cases., 2020)
Initially, UrbanClap-developed as a horizontal marketplace-faced intense competition from existing and new players operating in the hyperlocal service space. After struggling for a bit, the founders decided to restructure its portfolio and instead of providing more than 50 services, they focused it on 6. They standardized their services by offering a uniform scope of service at a fixed price, with the service delivered by UrbanClap-trained professionals using UrbanClap-specified standard products and equipment.